KINERJA PENYULUH PERTANIAN TERHADAP KELOMPOK TANI â€œSUKA MAJUâ€ DI DESA KOPIWANGKER KECAMATAN LANGOWAN BARAT - Grasela Venda Wosal; Martha Mareyke Sendow; Lorraine W. Th. Sondakh (AGRI-SOSIOEKONOMI, 2018)
This study aims to determine the performance of agricultural extension workers to â€œSuka Majuâ€ farmers groups in the village Kopiwangker sub-district, west Langowan. This research was conducted for two months from December 2016 to January 2017. The data used in this study are primary data and secondary data. Primary data obtained through direct interviews with members of the farmer group as many as 23 people based on questionnaires and secondary data obtained from the office of the agricultural, fisheries and forestry extension office (BP3K). The results of this study show that the performance of 2 agricultural extension workers in kopiwangker village is quite good with a score interpretation of 65.76%.*eprm*.